PERAN DINAS KEBUDAYAAN DAN PARIWISATA KOTA MATARAM DALAM MEMASARKAN DESTINASI PARWISATA KOTA MATARAM - Fatmawati, Fatmawati (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2024)
Marketing is a way of thinking about situations that balances the needs of tourists with the types of services or recreation available at a tourist attraction or destination. Information such as local geographic, historical, and cultural background, facilities and services, and costs should be available. Method This community service research activity uses a qualitative method by looking directly at the conditions of the Mataram City Tourism Office's role in marketing tourism destinations with a descriptive approach. The results of this research are to determine the role of the Mataram city tourism office in marketing destination tourism, namely first by conducting digital marketing through social media such as Instagram, Facebook and TikTok, secondly through activities held directly in the form of the Mataram festival. Pearl Festival, Mandalika Mataram Fair, Sharia Festival, terune dedare election, Eid al-Fitr, ogoh-ogoh-maulid. The Mataram City Tourism Office plays an important role in advancing Mataram City tourism through digital marketing and through events held in person.